Assessment of awareness of broiler chicken welfare in Gaborone, Botswana - Moreki, J. C.,; Maphanyane, P.,; Manyeula, F., (International Journal of Agricultural Technology, 2021)
Scientific information on broiler chicken welfare in Botswana is scarce. The awareness of poultry welfare in selected commercial broiler farms in Gaborone was assessed. A structured questionnaire was administered to 25 randomly selected farms and through direct observation. Results showed that mainly men (72%) were found actively involved in broiler chicken production. Ninety-six percent of the respondents strongly agreed that animal welfare is an important aspect in commercial poultry production. Furthermore, 64% of the respondents strongly agreed that welfare during transportation was good while 56% of the respondents strongly agreed that overcrowding affects welfare. Additionally, 80% of the respondents strongly agreed that beak trimming affects birds’ welfare, whereas 96% agreed that light affects performance of broiler chickens. Eighty-eight percent of the respondents strongly agreed that pre-slaughter management practices affect performance of birds. All the respondents in this study carried out vaccinations. Three heat sources were used during brooding and these are mbaula, electric heater and infra-red lamp. These results suggested that there is a need to educate broiler farmers on poultry welfare and how it affects the performance of birds